MAKNA PENDIDIKAN TAUHID DALAM BUKU “TUHAN MAHA ASYIK” KARYA SUJIWO TEJO DAN DR. MN. KAMBA - Muhammad Nur Abdurachman Wahid; Ahmad Shofiyuddin Ichsan (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2020)
The purpose of this study is to find out the meaning of tauhid (monotheistic) education in the book “Tuhan Maha Asyik” by Sujiwo Tejo and Dr. MN. Kamba and know the relevance of the meaning of tauhid in the book “Tuhan Maha Asyik” by Sujiwo Tejo and Dr. MN. Kamba on Islamic Religious Education. This study is library research. As for the data collection technique using documentation methods, while the data analysis technique used is content analysis from Paul Ricoeur's phenomenological hermeneutical analysis. The results of this study can be concluded that this book has the meaning of tauhid education that includes the meaning of tauhid, namely rububiah and uluhiyah. The meaning of tauhid in this book has relevance to several elements found in Islamic Education, namely in accordance with the purpose of Islamic Education which includes the meaning of ketauhidan (monotheism), understanding, appreciation, and practice.